The Influence of Information Technology, Organizational Structure, and Internal Control on the Quality of Management Accounting Information Systems in Banking in Tembilahan - Ranti Melasari; Afrizal Afrizal; Achmad Hizazi; Wiralestari Wiralestari (PT. Anagata Sembagi Education, 2026)
The quality of management accounting information systems plays a crucial role in supporting managerial decision-making processes in banking institutions. However, the effectiveness of these systems is influenced by various organizational factors, including information technology, organizational structure, and internal control. This study aims to analyze the influence of information technology, organizational structure, and internal control on the quality of management accounting information systems in banking institutions in Tembilahan, Indragiri Hilir Regency. This study uses a quantitative approach with a causal comparative research design. The study population consisted of managers working at eleven banking institutions in Tembilahan. The sampling technique used a saturated sampling method with 50 questionnaires distributed and 33 returned and processed questionnaires. Data collection techniques were carried out through questionnaires measured using a five-point Likert scale. Data analysis was carried out through descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS version 26 software. The results of the study indicate that information technology, organizational structure, and internal control partially have a positive and significant influence on the quality of management accounting information systems. Furthermore, simultaneous testing results indicate that the three variables collectively have a significant effect on the quality of management accounting information systems. The coefficient of determination indicates that 60.3% of the variation in the quality of management accounting information systems can be explained by the three independent variables studied. This finding underscores the importance of information technology integration, an effective organizational structure, and a strong internal control system in improving the quality and reliability of management accounting information systems in banking institutions.